Adhesion-dependent regulation of an A+U-rich element-binding activity associated with AUF1. - Sirenko, O I (1997)
Monocyte adherence results in the rapid transcriptional activation and mRNA stabilization of numerous mediators of inflammation and tissue repair. While the enhancer and promoter elements associated with transcriptional activation have been studied, mechanisms linking adhesion, mRNA stabilization, and translation are unknown. GROalpha and interleukin-1beta (IL-1beta) mRNAs are highly labile in nonadhered monocytes but stabilize rapidly after adherence. GROalpha and IL-1beta transcripts both contain A+U-rich elements (AREs) in the 3' untranslated region (UTR) which have been directly associated with rapid mRNA turnover. To determine if the GROalpha ARE region was recognized by factors associated with mRNA degradation, we carried out mobility gel shift analyses using a series of RNA probes encompassing the entire GROalpha transcript. Stable complexes were formed only with the proximal 3' UTR which contained the ARE region. The two slower-moving complexes were rapidly depleted following monocyte adherence but not direct integrin engagement. Deadherence reactivated the two largest ARE-binding complexes and destabilized IL-1beta transcripts. Antibody supershift studies demonstrated that both of these ARE RNA-binding complexes contained AUF1. The formation of these complexes and the accelerated mRNA turnover are phosphorylation-dependent events, as both are induced in adherent monocytes by the tyrosine kinase inhibitor genistein and the p38 MAP kinase inhibitor of IL-1beta translation, SK&F 86002. These results demonstrate that cell adhesion and deadhesion rapidly and reversibly modify both cytokine mRNA stability and the RNA-binding complexes associated with AUF1.